Modification of atmospheric extinction coefficient of non-line-of-sight ultraviolet communication under weak turbulence. (March 2015) - Li, Bifeng; Wang, Hongxing; Wu, Xiaojun; Song, Bo; Hu, Hao
Abstract: A calculation method of scintillation attenuation (SA) for non-line-of-sight (NLOS) ultraviolet (UV) communication is proposed on the basis of weak turbulence theory. To improve the channel model under turbulent environment, the atmospheric extinction coefficient in combination with UV single-scatter approximation model is modified based on SA. The in-depth analysis and interesting conclusion of atmospheric extinction coefficient named the turbulence coefficient versus different factors, including refractive-index structure parameter at the ground with measurement data, transceiver range and transceiver apex angles, are conducted. Abstract : Highlights: We propose a calculation method of scintillation attenuation for UV communication. Atmospheric extinction coefficient is modified based on scintillation attenuation. Refractive-index structure parameter has dynamic influence on turbulence coefficient. The optical geometry settings should be balanced due to turbulence effect.